Efficacy of cryogun versus diode laser therapy in the management of oral leukoplakia - K Naga Venkata Sai Praveen; Gajendra Veeraraghavan; T Ramesh; T Navya Teja; G Upendra; Y Kalyan (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: This study was aimed to clinically evaluate the effectiveness of 810 nm diode laser and cryosurgery in the management of oral leukoplakia (OL) in terms of healing outcomes. Materials and Methods: Thirty subjects clinically and histo-pathologically diagnosed as having OL were randomly allocated into two groups. Group-1 consisting of 15 subjects each treated with cryotherapy, Group-2 was treated with an 810 nm diode Laser. VAS scale was used for evaluating the postoperative discomfort due to pain and Bates- Jensen Wound Assessment Tool was used to evaluate clinical wound healing. Results: Data analysis was done by using one-way ANOVA for intragroup variations. For intergroup comparisons Paired t- test was used. A statistically significant number of recurrences was noticed in the cryo group compared to the LASER group. Conclusion: This study results suggest that both cryosurgery and laser therapy were effective in terms of patient comfort. However more number of recurrences and mild post operative edema in the cryo group make LASER therapy a better management option.